Pattern Analysis of Vegetation and Structure Mapping of Yard Plant in Gatak District, Sukoharjo - Sofyan Anif (Universitas Muhammadiyah Surakarta, 2003)
Target of research is to know 1) level of type variety (diversitas) and mount the closeness (densitas) of lawn crop which conducting in region of District of Gatak of Sub Province Sukoharjo; 2) pattern of mapping of lawn crop which conducting in region District of Gatak of Sub Province Sukoharjo of pursuant to variety level and its closeness. This research is field survey done with the method of multi stage that is stratified purposive of sampling and random sampling. Focus the survey is does the stocktaking of lawn crop which conducting in house lawn. To know the structure of vegetate data processed by using formula Cox (1989) to know the closeness level, while to know the level of species variety, data analyzed to use the index of diversities Simpson. Pursuant to result of inferential solution and research 1) result analyze the structure of vegetate of lawn crop indicate that (a) District Gatak have the level of high diversities lawn crop, with the index diversities of equal to 0,84159 and index predominate equal to 0,15841, and also highest PIE 0,20657 and PIE lowerest of equal to 0,00032. Species of lawn crop having high domination that is melinjo (Gnetum gnemon), (b) closeness of lawn crop at every countryside in District Gatak of included in category very meeting of because relied on by a closeness value of every countryside more than 75%. Crop found in research are having high closeness level for example: melinjo, banana, mango, rambutan, papaya, tapioca, and coconut, while crop having low closeness level for example: jambu mete, tapak doro, flower pukul empat; and 2) mapping of lawn crop cover the function value and amount of lawn crop found by a number of 57 type of lawn crop found in researh area, can be grouped to become 5 faction that is drug crop, vegetable faction, fruit crop, decorative crop, and protector crop.